2008
DOI: 10.1002/cmmi.229
|View full text |Cite
|
Sign up to set email alerts
|

Efficient stem cell labeling for MRI studies

Abstract: Iron oxide particles are especially suited for cell tracking experiments due to their extraordinarily molar relaxivity as compared with other paramagnetic nuclei. We have compared different iron oxide particles (Sinerem, Endorem and magnetic microspheres) for their suitability to label embryonic stem cells (D3 cell line). In addition to detectability thresholds, particular attention has been paid to the evaluation of long-term stability of the labelling procedure (up to 4 weeks) as well as to toxic and other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 37 publications
5
96
0
Order By: Relevance
“…Numerous studies have shown that in vitro neural stem and progenitor cells can be loaded with iron oxyde particles (for review CouillardDespres & Aigner 2011). It has been suggested that this method has a very low detection threshold (Kustermann et al 2008). One limitation of this method is that the detected contrast on MR images refers only to the particles and not to the labelled cells themselves.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Numerous studies have shown that in vitro neural stem and progenitor cells can be loaded with iron oxyde particles (for review CouillardDespres & Aigner 2011). It has been suggested that this method has a very low detection threshold (Kustermann et al 2008). One limitation of this method is that the detected contrast on MR images refers only to the particles and not to the labelled cells themselves.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…This is mainly due to dilution of (U)SPIOs with cell division but might also occur due to exocytosis phantoms in vitro, can also be monitored by MRI following transplantation in vivo. When grafted in either of the particles (24). The PDT of mESC and rMAPC was 12 h, whereas the PDT for mMSC was 48 h, which mouse or rat brain, with or without stroke, labeled rMAPC were visualized until 15 days after transplantaexplains the significant reduction of iron in rMAPC.…”
Section: Phenotype and Genetic Integrity Effect Of Labeling On Stem mentioning
confidence: 99%
“…The majority of studies have used iron oxide-based nanoparticles (NPs) due to their relatively high sensitivity and their acceptable biocompatibility. 15,17,18,24,25,26 Several studies have evaluated potential toxic or adverse effects of intracellular iron oxide in cells, where the major focus has been the comparison of different NP-related properties (size, coating, and concentrations). 25,27 Furthermore, in studies where material-related properties have been the subject of scrutiny, cell-related properties have rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%